Comparison of germination abilities of Centaurea sp. under in vivo and in vitro conditions - Demirel, Sevda; Türkoğlu, Nalan; Özdemir, Fethi Ahmet (Progress in Nutrition, 2017)
In this study, in vivo and in vitro germination of endemic and under-threat Centaurea fenzlii and Centaurea derderifolia species were investigated. In in vivo germination, seeds were spread with forceps over the drying papers moisturized with distilled water in petri dishes. Then, petri dishes were closed and taken for germination in a climate chamber at 25°C and 16 hours light/8 hours dark photoperiods. In in vitro germination, following the sterilization period, seeds were cultured in MS, B5, SH and WH growth medium with 6 seeds in each in a climate chamber at 25°C under 16 hours light/8 hours dark photoperiod. Present findings revealed high germination rates for C. fenzlii and C. derderifolia seeds in WH growth medium.